Complex organic molecules in the Galactic Centre: the N-bearing family. Issue 3 (4th May 2018) - Zeng, S; Jiménez-Serra, I; Rivilla, V M; Martín, S; Martín-Pintado, J; Requena-Torres, M A; Armijos-Abendaño, J; Riquelme, D; Aladro, R
ABSTRACT: We present an unbiased spectral line survey towards the Galactic Centre (GC) quiescent giant molecular cloud, G+0.693 using the GBT and IRAM 30  telescopes. Our study highlights an extremely rich organic inventory of abundant amount of nitrogen (N)-bearing species in a source without signatures of star formation. We report the detection of 17 N-bearing species in this source, of which eight are complex organic molecules. A comparison of the derived abundances relative to H2 is made across various Galactic and extragalactic environments. We conclude that the unique chemistry in this source is likely to be dominated by low-velocity shocks with X-rays/cosmic rays also playing an important role in the chemistry. Like previous findings obtained for O-bearing molecules, our results for N-bearing species suggest a more efficient hydrogenation of these species on dust grains in G+0.693 than in hot cores in the Galactic disc, as a consequence of the low-dust temperatures coupled with energetic processing by X-ray/cosmic ray radiation in the GC.